Nephron-Sparing Laparoscopic versus Open Surgery for T1 Renal Mass: Seven Years’ Experience and Outcomes (Journal of Current and Advance Medical Research, 2021)
Background: Nephron-sparing surgery is an accepted treatment modality for renal cell carcinoma (RCC) in certain situations.Objectives: The aim of this study was to compare perioperative outcomes after laparoscopic and open partial nephrectomy for patients with a solitary renal tumors of 7cm or less in different institutes in Dhaka.Methodology: Between June 2013 and October 2020, 23 patients had undergone LPN and 24 patients had undergone OPN for the treatment of solitary renal tumors of 7cm or less in different institutes in Dhaka. Large renal mass (>7cm), multiple tumor and patients with complex renal anatomy were excluded from this study. Patients having previous abdominal surgery were excluded from LPN and all LPN were performed transperitoneally.Results: Although the mean operative time was longer in the LPN than in the OPN group (134.4±35.36 (45-180) minutes versus 110.56±35.36 (60-165) minutes; P